Technologies to recover exhaust heat from internal combustion engines - Saidur, Rahman; Rezaei, Mahdi; Muzammil, Wan Khairul; Masjuki, Haji Hassan; Paria, Saman; Hasanuzzaman, Md. (Elsevier, 2012)
The focus of this study is to review the latest developments and technologies on waste heat recovery of exhaust gas from internal combustion engines (ICE). These include thermoelectric generators (TEG), organic Rankine cycle (ORC), six-stroke cycle IC engine and new developments on turbocharger technology. Furthermore, the study looked into the potential energy savings and performances of those technologies. The current worldwide trend of increasing energy demand in transportation sector are one of the many segments that is responsible for the growing share of fossil fuel usage and indirectly contribute to the release of harmful greenhouse gas (GHG) emissions. It is hoped that with the latest findings on exhaust heat recovery to increase the efficiency of ICEs, world energy demand on the depleting fossil fuel reserves would be reduced and hence the impact of global warming due to the GHG emissions would fade away.